Scaling Up Economic Inclusion Programs in Urban Areas - Avalos, Jorge Eduardo; Chaudhary, Sarang; Clay, Timothy Joseph Peter; Dutta, Puja Vasudeva (Washington, DC: World Bank, 2022)
This PEI In Practice Brief provides an overview of volumes 1 and 2 of PEI In Practice on Economic Inclusion in urban areas. Links to both volumes are provided for additional reading.